Chemical composition and hypocholesterolemic effect of milk kefir and water kefir in Wistar rats - ROCHA-GOMES, Arthur; ESCOBAR, Amanda; Silva SOARES, Jéssica; Alves da SILVA, Alexandre; Andrade Villela DESSIMONI-PINTO, Nísia; RIUL, Tania Regina (Revista de Nutrição, 2023)
Objective To compare the effects of fermented kefir on the nutritional, physiological, and biochemical parameters of rats. Methods Grains of milk kefir (whole and skimmed) and water kefir (brown sugar) were used. The chemical composition analysis was performed on substrates and fermented beverages. The rats were evaluated for weight gain, body mass index, as well as their food, water, kefir, and calorie intake. We also evaluated their energy efficiency coefficient, weight of organs, in addition to their serum, and hepatic biochemistry. Results Fermentation increased the acid content index owing to degradation of lactose and brown sugar. The animals consumed more kefir, reducing the intake of chow and water. Kefir did not alter body and organ weight, while improving the lipid profile. Conclusion Water kefir with brown sugar was more effective in improving the lipid profile.